Economic transformation in Ghana: Where will the path lead? - Kolavalli, Shashidhara; Robinson, Elizabeth J. Z.; Diao, Xinshen; Alpuerto, Vida; Folledo, Renato; Slavova, Mira; Ngeleza, Guyslain K.; Asante, Felix Ankomah (Pennsylvania State University Press, 2012)
In the context of the Ghanaian government's objective of structural transformation with an emphasis on manufacturing, this paper provides a case study of economic transformation in Ghana, exploring patterns of growth, sector transformation, and agglomeration. We document and examine why, despite impressive growth and poverty reduction figures, Ghana's economy has exhibited less transformation than might be expected for a country that has recently achieved middle-income status. Ghana's reduced share of agriculture in the economy, unlike many successfully transformed countries in Asia and Latin America, has been filled by services, while manufacturing has stagnated and even declined. Likely causes include weak transformation of the agricultural sector and therefore little development of agro-processing, the emergence of “consumption cities” and consumption-driven growth, upward pressure on the exchange rate, weak production linkages, and a poor environment for private-sector-led manufacturing.